2016
DOI: 10.1177/0969733016658792
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and its influencing factors: A cross-sectional study in China

Abstract: Our conclusion suggests that hospital and organizational administrations should attach much importance to the moral distress experienced by clinical nurses in China. Further studies should focus on interventions about how to reduce the levels of the frequency and intensity of moral distress among clinical nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 38 publications
(47 reference statements)
2
55
2
9
Order By: Relevance
“…In line with the present study, Fumis in Brazil [26], Allen in the United States [27] and Karagozoglu in Turkey [28] all showed some degree [29], Etebari in Ardabil [30], Sadeghi in Shahroud [31], and Ashktorab in Tehran [32] showed the moral distress in nurses. While Wenwen et al in China [33] confirmed less moral distress in nurses in intensive care units. The results of other studies also showed less range of moral distress in nurses in intensive care units [34][35][36].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with the present study, Fumis in Brazil [26], Allen in the United States [27] and Karagozoglu in Turkey [28] all showed some degree [29], Etebari in Ardabil [30], Sadeghi in Shahroud [31], and Ashktorab in Tehran [32] showed the moral distress in nurses. While Wenwen et al in China [33] confirmed less moral distress in nurses in intensive care units. The results of other studies also showed less range of moral distress in nurses in intensive care units [34][35][36].…”
Section: Discussionmentioning
confidence: 94%
“…In terms of income, the results of Wenwen's study in China showed a significant relationship between moral distress and monthly income; as income increased, so did moral tensions [33]. Instead of examining the monthly income level of nurses, some research has examined employment status [32,37], which in itself can be a sign of job stability and better income of permanent employees than others.…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura discute-se se a enfermagem será uma profissão mais predisposta ao sofrimento por ser maioritariamente feminina. Alguns estudos revelam maiores índices de sofrimento no sexo feminino (Trautmann, Epstein, Rovnyak, & Snyder, 2015) e outros no sexo masculino, mas a maioria não aponta para diferenças significativas entre os sexos (Woods, Rodgers, Towers, & Grow, 2015;Xiaoyan, Yufang, Lifeng, & Congcong, 2016 constatou que os enfermeiros com menos tempo de serviço apresentavam mais sofrimento. No que respeita a estas variáveis, a literatura não é consensual, sendo que alguns estudos apontam relações significativas com a idade e tempo de serviço (Woods et al, 2015), enquanto noutros esta relação não se verifica (Lusignani, Gianni, Re, & Buffon, 2016).…”
Section: Discussionunclassified
“…A falta de recursos é um elemento que põe em risco o cumprimento do compromisso moral profissional do enfermeiro, qual seja, prestar o melhor cuidado de enfermagem. Quando o enfermeiro percebe que a falta de recursos acarreta prejuízo para os resultados do paciente, o sofrimento moral é inevitável (Wolf, et al, 2016 (Xiaoyan, Yufang, Lifeng, & Congcong, 2016). A literatura afirma que o sofrimento moral costuma ser maior em contextos hospitalares, quando comparado com outros serviços, como os de atenção primária à saúde (Eizenberg, Desivilya, & Hirschfeld, 2009), assim, o nível moderado e baixo de sofrimento moral deste estudo pode resultar dessa diferença de médias entre serviços.…”
Section: Discussionunclassified
“…A literatura discute se a enfermagem estaria mais predisposta a vivência do sofrimento moral por ser uma profissão majoritariamente feminina. A ligação entre sofrimento moral e gênero não é clara, com estudos mostrando maiores índices em mulheres (Trautmann, Epstein, Rovnyak, & Snyder, 2015), outros em homens (Dyo, Kalowes, & Devries, 2016), enquanto que a maioria não demonstra diferenças significativas entre eles (Xiaoyan, Yufang, Lifeng, & Congcong, 2016) (Woods, Rodgers, Towers, & Grow, 2015) (Borhani, Mohammadi, & Roshanzadeh, 2015).…”
Section: Tabela 10 -Variáveis Relativas Ao Local De Trabalho Dos Enfeunclassified